794 Contribution of sleep disorders to dementia incidence following traumatic brain injury: A decade-long retrospective cohort study. (3rd May 2021) - Mollayeva, Tatyana; Hurst, Mackenzie; Escobar, Michael; Colantonio, Angela
Abstract: Introduction: We aimed to examine the association between sleep disorders and dementia risk in a population-based cohort of adult male and female patients with traumatic brain injury (TBI). Methods: We studied a province-wide retrospective cohort of all adult patients (≥ 18 years) free of dementia at the admission to the emergency department or acute care hospital with diagnoses of TBI between May 2003 and April 2013. All patients were followed through until May 2016. The primary exposure was a sleep disorder, and the primary outcome was dementia, both defined by the International Classification of Diseases, tenth revision diagnosis. Associations of sleep disorders with dementia were analyzed in multivariate Cox Proportional Hazard modeling. Results: In total, 712, 708 patients with TBI of all severities were included in this study. Their median age was 44 years, 59% were males. Over a median follow-up of 52 months (interquartile range, 19–86 months), 32, 834 (4.6%) developed dementia. Controlling for age, sex, income level, injury severity, and known comorbidity risks, diagnosed sleep disorder was a significant predictor of incident dementia: hazard ratio (HR), 1.250 [95% CI, 1.146–1.363]. When results were stratified by sex, the association of sleep disorder with dementia remained significant in male: HR 1.255 [95% CI, 1.112–1.415] and in female patients: HR 1.234 [95% CI, 1.088–1.400]. Sensitivity analyses on Alzheimer's disease case definition and using Fine and Gray competing risk models confirmed the association between sleep disorder and dementia in both sexes. Conclusion: In both sexes, sleep disorders were independently associated with dementia onset (adjusted HRs>1.2). Thus, screening for sleep disorders should be part of regular care for TBI patients, as with the steady increase of TBI survivorship and life expectancy, undiagnosed sleep disorders can initiate a new cascade of cognitive deficits independent from TBI. Support (if any): This work was supported by the postdoctoral research grant from the Alzheimer's Association (AARF-16-442937) to T.Mollayeva. The authors were also supported by the Eunice Kennedy Shriver National Institute of Child Health & Human Development of the National Institutes of Health under Award Number R21HD089106 and the Canadian Institutes for Health Research Grant–Institute for Gender and Health (#CGW-126580).